Long-term administration of angiotensin (1–7) prevents heart and lung dysfunction in a mouse model of type 2 diabetes (db/db) by reducing oxidative stress, inflammation and pathological remodeling. (May 2016) - Papinska, Anna M.; Soto, Maira; Meeks, Christopher J.; Rodgers, Kathleen E.
Graphical abstract: Abstract: Congestive heart failure is one of the most prevalent and deadly complications of type 2 diabetes that is frequently associated with pulmonary dysfunction. Among many factors that contribute to development and progression of diabetic complications is angiotensin II (Ang2). Activation of pathological arm of renin-angiotensin system results in increased levels of Ang2 and signaling through angiotensin type 1 receptor. This pathway is well recognized for its role in induction of oxidative stress (OS), inflammation, hypertrophy and fibrosis. Angiotensin (1–7) [A(1–7)], through activation of Mas receptor, opposes the actions of Ang2 which can result in the amelioration of diabetic complications; enhancing the overall welfare of diabetic patients. In this study, 8 week-old db/db mice were administered A(1–7) daily via subcutaneous injections. After 16 weeks of treatment, echocardiographic assessment of heart function demonstrated significant improvement in cardiac output, stroke volume and shortening fraction in diabetic animals. A(1–7) also prevented cardiomyocyte hypertrophy, apoptosis, lipid accumulation, and decreased diabetes-induced fibrosis and OS in the heart tissue. Treatment with A(1–7) reduced levels of circulating proinflammatory cytokines that contribute to the low grade inflammation observed in diabetes. In addition, lung pathologies associated with type 2 diabetes, including fibrosis and congestion, were decreased with treatment. OS and macrophage infiltration were also reduced in the lungs after treatment with A(1–7). Long-term administration of A(1–7) to db/db mice is effective in improving heart and lung function in db/db mice. Treatment prevented pathological remodeling of the tissues and reduced OS, fibrosis and inflammation.